The systemic approach in sociology and Niklas Luhmann : expectations, discussions, doubts - Šubrt, Jiří (Bingley, U.K. : Emerald Publishing Limited, 2020)
This book is a comprehensive overview of the theoretical discussion of one of most important conceptions in sociology at the end of 20th century - the theory of social systems. The spotlight of this book falls on the work of Niklas Luhmann and his holistic approach. Current modern society is, for Luhmann, a functionally differentiated society, which means that a number of specialized societal sub-systems (politics, economics, religion, law, science, art etc) have formed. Each system is based on its own type of communication led by its own generalized communicative media. Luhmann controversially depicts modern society as a plurality of many societal subsystems operating without a top and without a coordinating and managing centre. This book weighs the strong and weak features of the systemic approach in sociology and discusses ways to rethink it.
Chapter 1. Dream or myth? (introduction) -- Chapter 2. The dream of a united conception of science -- Chapter 3. What is the right starting point for sociological thought? -- Chapter 4. A dream of integration of theory and society (Parsons) -- Chapter 5. The dream of the sociological super-theory (Luhmann) -- Chapter 6. Reflections on possibilities of application of system approach at macrosocial level.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Social systems -- Philosophy; System theory -- Philosophy; Parsons, Talcott, -- 1902-1979.; Social Science -- General; Social groups